2013
DOI: 10.1016/j.physletb.2013.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Rotating regular black holes

Abstract: The formation of spacetime singularities is a quite common phenomenon in General Relativity and it is regulated by specific theorems. It is widely believed that spacetime singularities do not exist in Nature, but that they represent a limitation of the classical theory. While we do not yet have any solid theory of quantum gravity, toy models of black hole solutions without singularities have been proposed. So far, there are only non-rotating regular black holes in the literature. These metrics can be hardly te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
443
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(447 citation statements)
references
References 40 publications
4
443
0
Order By: Relevance
“…All the subtleties of the nonlinear effects were discussed in [15][16][17][18]. Rotating regular black hole solutions have been introduced in [19][20][21][22][23][24]. Similarly to the Kerr or Reissner-Nordström solutions of the standard general relativity that describe both black holes and naked singularities, the regular solutions describe both the black hole and no-horizon spacetimes demonstrating strong gravity effects [25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…All the subtleties of the nonlinear effects were discussed in [15][16][17][18]. Rotating regular black hole solutions have been introduced in [19][20][21][22][23][24]. Similarly to the Kerr or Reissner-Nordström solutions of the standard general relativity that describe both black holes and naked singularities, the regular solutions describe both the black hole and no-horizon spacetimes demonstrating strong gravity effects [25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…[29,30]. Given a Hayward black hole of mass M and angular momentum J = Ma, the metric is in Boyer-Lindquist coordinates…”
Section: Hayward Black Holementioning
confidence: 99%
“…Based the weak cosmic censorship conjecture, the singularity should be hidden by the event horizon of the black hole, but the Hayward black hole has no singularity within the horizon. Using the Newman-Janis transformation [30], the rotating Hayward black hole is obtained. The metric of the Hayward black hole is also found in the gravity theory coupled with non-linear electrodynamics [31].…”
Section: Introductionmentioning
confidence: 99%
“…[6], it is formed by a nonlinear electrodynamic field. RBH solutions with axial symmetry have been constructed as well (see the recent works [7][8][9][10][11][12][13]). Contrary to the spherical case, we have shown that axisymmetric RBHs always violate the WEC [10].…”
Section: Introductionmentioning
confidence: 99%